Revelation's Visionary Challenge to Ordinary Empire - Koester, Craig R. (Interpretation, 2009)
Revelation addresses the ordinary challenges facing Christians under Roman rule, rather than speaking only to those enduring a time of terror. Some of the readers were struggling, but others were affluent and complacent. The book's visions seek to alter the way they see the political, religious, and economic dimensions of imperial life and to call them to renewed faithfulness to God and the Lamb.